Electron backscattering for signal enhancement in a thin‐film CdTe radiation detector. Issue 10 (17th August 2022) - Akbari, Fatemeh; Shvydka, Diana
Abstract: Background: Thin‐film cadmium telluride (CdTe) offers high average electron density, direct detection configuration, and excellent radiation hardness, making it an attractive material for radiation detectors. Although a very thin detector provides capabilities to conduct high‐resolution measurements in high‐energy radiation fields, it is limited by a low signal, often boosted with a front metal converter enhancing X‐ray absorption. An extension of this approach can be explored through the investigation of electron backscattering phenomenon, known to be highly dependent on the material atomic number Z . Adding an electron reflector in tandem with the back electrode is proposed to be utilized for the detector signal enhancement. Purpose: We investigated the possibility of augmenting the fluence of electrons traversing CdTe thin film and thus increasing the detected signal pursuing two pathways: (1) adding a high‐ Z metal layer to the back of the detector surface, and (2) adding a top low‐ Z material to the detector layer to return its backscattered electrons. Copper (Cu) and lead (Pb) layers of varying thickness were investigated as potential metal back‐reflectors, whereas polymethyl methacrylate (PMMA) water phantom material was tested as the top cover in multilayer detector structures. Methods: The Monte Carlo (MC) radiation transport package MCNP5 was first used to model a basic multilayer structure of a CdTe‐sensitive volume surrounded by PMMA, under a 6‐MV photon beam. Addition of Cu or Pb back‐reflectors allowed for the analysis of the signal enhancement and associated changes in Compton electrons fluence spectra. Related backscattering coefficients were then calculated using EGSnrc MC user‐code for monoenergetic electron sources. Analytical functions were established to represent the best fitting curves to the simulation data. Finally, electron backscattering data was related to signal enhancement in the CdTe sensitive layer based on a semiquantitative approach. Results: We studied multilayer detector structures, decoupling the effects of PMMA and the back‐reflector metals, Cu or Pb, on electron backscattering for electron energy range of up to 500 keV or 1 MeV depending on the choice of metal. Adding a 100–200‐µm‐thick metal film below the detector sensitive volume increased the fraction of reflected electrons, especially in the low, 100–200 keV, energy range. The thickness dependence of backscattering coefficients from thin films exhibits saturations at values significantly exceeding the electron ranges. That effect was related to the large‐angle electron scattering. A detailed simulation of energy deposition revealed that the modified structures using Cu and Pb increased energy deposition by ∼10% and 75%, respectively. We have also established a linear dependence between the energy deposition in the semiconductor layer and the fluence of backscattered electrons in the corresponding multilayer structure. The low‐ Z top layer in practically implemental thicknesses of tens of micrometers has a positive effect due to partial electron reflection back to the semiconductor layer. Conclusions: Signal enhancement in a thin‐film CdTe radiation detector could be achieved using electron backscattering from metal reflectors. The methodology explored here warrants further studies to quantify achievable signal enhancement for various thin films and other small sensitive volume detectors.